Health profiling of elderly in Gujarat: evidences from longitudinal ageing study in India - Desai, Gayatri S.; Ghosh, Koustav (International Journal Of Community Medicine And Public Health, 2023)
Background: Considering the burden of different health related disorders amongst the elderly, the present study aims to examine the health profile and the factors associated with various health issues among the elderly in Gujarat. Methods: The current study has used the Longitudinal Ageing Study in India (LASI) Wave-1 data. The chi-square test and logistic regression model have been used to establish the association between the study variables and factors associated with the chronic diseases among elderly in Gujarat. Results: The prevalence of chronic diseases among elderly in Gujarat is 51.3 percent. Hypertension was the highest prevalent disease suffered by nearly one-fourth (24.3%) of the elderly people covered under the study followed by prevalence of chronic bone/joint diseases (15.7%) and diabetes (12.4%). The present study showed that the risk of occurrence of chronic diseases increases along with the age. Consumption of alcohol increases the risk of chronic morbidities. On the other hand, education, work status and physical activity play significant role in reducing the prevalence of chronic diseases. Conclusions: The study highlights the prevalence of different health related disorders amongst the elderly in Gujarat. In addition to this, the study tries to identify the critical factors associated with health issues of elderly. The findings from the study can also help in strengthening the scope of National level preventive and health care programme for the elderly population in Gujarat.